Calculation of reinforced-concrete frame strength under a simultaneous static cross section load and a column lateral impact - Belov N. N. Nikolay Nikolaevich; Yugov N. T.; Kopanitsa D. G. Dmitry Georgeevich; Kopanitsa G. D. Georgy Dmitrievich; Yugov A. A. Aleksey Aleksandrovich; Kaparulin S. L. Sergey Lvovich; Plyaskin A.; Kalichkina A.; Ustinov A. (2016, 2016)
Title screen